Introduction: The Social Responsibility of Lawyers - Karen Tokarz (Washington University Journal of Law & Policy, 2007)
Like the prior eight volumes dedicated to Access to Justice, most of the Articles and Essays in this volume are written by presenters in the School of Law’s annual Public Interest Law & Policy Speaker Series, entitled “Access to Justice: The Social Responsibility of Lawyers.” These presenters are prominent academics, practitioners, and authors from diverse backgrounds in areas such as international human rights, the economics of poverty, racial justice, immigration, capital punishment, conflict resolution, clinical legal education, government public service, and pro bono private practice, who share a commitment to access to justice. The Public Interest Law & Policy Speaker Series was developed in 1998–99 in celebration of the School’s nationally recognized Clinical Education Program, through which many of our students are introduced to public service and public interest law practice. The Series informs the Washington University community and wider community on issues of justice through the presentations of the speakers (that are posted on the law school’s web site), through the Articles drawn from the presentations that are published in the Journal, and through the seminar course that accompanies the series in which students have the opportunity to meet with the speakers, read their work, and develop papers that focus on the speakers’ ideas.
Keywords: Access to justice; Sociological jurisprudence; Social justice; Government policy; Rule of law; Emigration & immigration -- Government policy; September 11; 2001; War on Terrorism; National Environmental Policy Act of 1969 (NEPA); Opium trade; Afghanistan -- History; Arkansas; Tort reform